Motion Graphics Containing Education for Sustainable Development: A Research Development of Instructional Media for Elementary School Students - Setiadi, Pidi; Alia, Dwi; Nurzaman, Istikhoroh (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2023)
The emergence of issues of species extinction, pollution, scarcity, and others need to be addressed by everyone, including educators. One solution is the use of motion graphics-based learning media. This research was conducted to describe design development, design validity, and the effectiveness of motion graphic designs with content related to Education for Sustainable Development. The research method used is Design-Based Research. The stages of this research include identifying and analyzing problems for initial development needs, designing motion graphics media designs, implementing, reflecting, and making the final product. This research was conducted at the UPI Campus Tasikmalaya partner school. The results of the study found that motion graphics which contain Education for Sustainable Development are very useful as a medium for learning the functions of attention and affection significantly. Motion graphics duration of no more than 3-5 minutes is sufficient to focus students' attention on learning more deeply about human activity with a sustainable perspective. However, it was also found that this short duration limits the richer educational content related to Education for Sustainable Development, so it is recommended to use motion graphics in combination with learning media and other teaching materials.